Desenvolvimento de farinha de xiquexique (Pilosocereus gounellei): caracterização nutricional, propriedades funcionais e sua utilização na elaboração de cookies - Machado, Tamires Alcântara Dourado Gomes (2019)
Pilosoreceus gounellei is an excellent matrix for the development of new products, has relevant nutritional properties, and presents bioactive compounds that enrich the final product. This study aimed to develop xiquexique flours with different granulometries and treatments, to study their nutritional and rheological properties, as well as to evaluate the potential of their application in cookies. It was elaborated 4 flours and 4 cookies: F1 (xiquexique flour without heat treatment sieved in a 100 mesh sieve), F2 (xiquexique flour without heat treatment sieved in 28 mesh sieve), FA1 (Xique- autoclaved xyche sieved in a 100 mesh sieve), FA2 (Autoclaved xiquexique flour sieved in 28 mesh sieve), C1 (conventional control cookie), C2 (conventional xiquexique cookie), C3 C4 (Comprehensive xiquexique cookie). For the flours, microbiological, physical, physicochemical, amino acid profile, sugar profile, mineral profile, rheological properties, anti-nutritional factors and antioxidant activity were performed. Cookies were evaluated for physical, physical-chemical characteristics, texture, expansion index and sensory attributes. In relation to the xiquexique flours, the values of acidity, pH and water activity are in accordance with the characteristic range of the flour and indicate good stability during storage. Flours presented low moisture content (3.08 - 5.06%) and fat (0.48 - 0.95%); high fiber content (16.59 - 44.43%), starch (28.77 - 65.24%) and ash (8.36 - 12.34%); and medium protein content (3.06 - 5.75%). They were rich in minerals, mainly calcium, iron, potassium, magnesium and manganese. They presented gel color and gel turbidity characteristic of flour. Rheological analysis revealed that the flour has high viscosity and texture of the gels, being an excellent ingredient that can be used as a thickening agent or gelling agent in various food products. In addition, the flours presented compounds with antioxidant activity and in the DNA protection test it was possible to observe a protective behavior in all the samples, signaling the probable antioxidant potential of xiquexique flours. Antinutritional factors were detected in low amounts when compared to other plant foods, and therefore not presenting a disadvantage. Autoclaving and granulometry influenced the physical, physical-chemical and rheological parameters, but did not reduce the potential for flour use, but only as characteristics to be considered in the choice of products for which they will be destined. Regarding cookies, water activity and moisture values were low, indicating good stability during storage. Cookies of xiquexique presented higher contents of ashes (2.47-2.74%), proteins (0.94-1.36%), fibers (4.41-8.10%) and resistant starch (3 , 65-2.10%) than their respective cookie controls. In addition, they have been rich in minerals, especially calcium, iron, potassium, magnesium and manganese, and can help consumers meet the daily needs of these essential nutrients. The luminance and texture characteristics of the xiquexique cookies were higher, while the expansion index was lower than the cookies controls. In sensory terms, they showed good acceptance and consumption intensity, in addition the results of the CATA can be used to improve the formulation. Thus, it can be concluded that xiquexique is an excellent food matrix for the development of flour with high nutritional and technological potential. Besides being an excellent ingredient for the production of cookies, it can also be interesting for application in various products, such as cream cheese. Therefore, the development of xiquexique flour appears to be an attractive initiative to obtain practical bakery products with nutritional quality, functional and attractive to consumers, such as cookies.